Methylmercury displays pro-adipogenic properties in rainbow trout preadipocytes. (January 2021) - Tinant, Gilles; Neefs, Ineke; Das, Krishna; Rees, Jean-François; Larondelle, Yvan; Debier, Cathy
Abstract: Methylmercury (MeHg) is a ubiquitous contaminant largely found in aquatic environments, especially in species at high trophic level such as salmonids. The aim of this study was to evaluate the effects of MeHg on adipocyte differentiation and lipid metabolism in rainbow trout. Primary cultured preadipocytes were exposed to increasing concentrations of MeHg during six days with or without a hormonal cocktail. Main results showed a dose-dependent intracellular accumulation of neutral lipids with a preferential uptake of n-3 polyunsaturated fatty acids. Interestingly, this accumulation occurred after a fairly low uptake of MeHg by preadipocytes and was maintained after the cellular exposure to MeHg. In membrane phospholipids, arachidonic acid (20:4 n-6) was released in a dose-dependent manner. At the transcriptional level, the expression of several adipocyte-specific genes (perilipin 2 and apolipoprotein Eb) as well as lipid-related genes (fatty acid synthase and fatty acid binding protein 11a) was up-regulated in preadipocytes exposed to MeHg. These results highlight for the first time the disrupting effect of MeHg in trout adipocyte metabolism, providing new insights regarding the role of environmental pollutants in adipose tissue dysfunction and related pathologies. Highlights: MeHg induced a dose-dependent accumulation of neutral lipids in preadipocytes. Accumulation of lipids persisted beyond the cellular exposure to MeHg. MeHg increased n-3 PUFA levels in lipid droplets and dropped AA levels in membranes. Expression of adipocyte- and lipid-specific genes was modulated by MeHg. Total mercury accumulated in cells was released when MeHg exposure stopped.